Evaluation and Analysis of Brawijaya University Sustainability Report Based on GRI Standards - Yuli Puji Astuti; Eko Ganis Sukoharso; Zaki Bariduwan (Journal of Applied Business, Taxation and Economics Research, 2023)
One of the derivatives of the practice of sustainability accounting is disclosing financial information, social information and environmental information in the form of a sustainability report. This study aims to evaluate sustainability reports at the university level based on the GRI Standards. This study uses a qualitative paradigm with data collection techniques using observation and document analysis. To analyze sustainability reports, this study used GRI Standards 2016. The results of this study concluded that the level of adherence to sustainability reports at Universitas Brawijaya was categorized as Well Applied because it was able to disclose GRI Standard indicators with a total disclosure of 86.03%. This result can be interpreted that the public sector, especially universities, has a very good ability to apply the concept of sustainability and can adopt the standard GRI in preparing its sustainability reports.